2017
DOI: 10.1002/2017wr021234
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Aquifer Vulnerability From Subsurface Fluid Injection at a Proposed Shale Gas Hydraulic Fracturing Site

Abstract: Groundwater flow resulting from a proposed hydraulic fracturing (fracking) operation was numerically modeled using 91 scenarios. Scenarios were chosen to be a combination of hydrogeological factors that a priori would control the long‐term migration of fracking fluids to the shallow subsurface. These factors were induced fracture extent, cross‐basin groundwater flow, deep low hydraulic conductivity strata, deep high hydraulic conductivity strata, fault hydraulic conductivity, and overpressure. The study consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 45 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…In fact, core-plug and well-test scales substantially coincide (K well-test /K core-plug 1.1-1.3) at such depth in the Triassic fluvial deposits of the St Bees Sandstone of the eastern Irish Sea Basin and in the Stuttgart Formation of the North German Basin (Förster et al 2006;Medici et al 2018). Nevertheless, subhorizontal (0-15°) bedding plane fractures up to~1 km depth contribute to enhance flow anisotropy favouring flow in directions parallel to the beds, leading to aquifer anisotropy that impedes rise of contaminants related to shale gas extraction at such elevated depths (Cai and Ofterdinger 2014;Wilson et al 2017).…”
Section: Synthesis Of Hydraulic Behaviour Of Continental Successionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, core-plug and well-test scales substantially coincide (K well-test /K core-plug 1.1-1.3) at such depth in the Triassic fluvial deposits of the St Bees Sandstone of the eastern Irish Sea Basin and in the Stuttgart Formation of the North German Basin (Förster et al 2006;Medici et al 2018). Nevertheless, subhorizontal (0-15°) bedding plane fractures up to~1 km depth contribute to enhance flow anisotropy favouring flow in directions parallel to the beds, leading to aquifer anisotropy that impedes rise of contaminants related to shale gas extraction at such elevated depths (Cai and Ofterdinger 2014;Wilson et al 2017).…”
Section: Synthesis Of Hydraulic Behaviour Of Continental Successionsmentioning
confidence: 99%
“…In contrast, residual flow through bedding-plane discontinuities at greater depths (~150-1,500 mBGL) favours horizontal fluxes of contaminants and retards upward migration associated with steeply inclined faults (Wilson et al 2017). Yet, both core-plug-scale and welltest-scale data are required jointly to effectively quantify the impact of geological heterogeneities on flow.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al (2017) showed that compartmentalisation may increase the risk of injected fluids migrating to near‐surface aquifers. In the study region, the Woodsfold fault is considered to compartmentalise the central and southern Fylde (Ove Arup and Partners Ltd., 2014a; Wilson et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…was because the modelled low-permeability faults acted to structurally compartmentalise groundwater in the basin, discouraging lateral flow and encouraging upward flow through strata in the presence of a vertical hydraulic head gradient. 14…”
Section: Thismentioning
confidence: 99%
“…[8][9][10][11][12][13] However, more recent numerical modelling found that for fluid injection situated between faults (a more likely development scenario because operators aim to avoid fluid injection into faults), it was the scenarios with low-permeability faults that resulted in the highest risk to the shallow aquifer. 14…”
Section: Introductionmentioning
confidence: 99%